Boundary-Crossing Movements: A Resource for Student Learning - Cattaruzza, Elisa; Kloetzer, Laure; Iannaccone, Antonio (Frontiers in Education, 2022)
This paper focuses on the learning processes of students involved in a pedagogical design bridging in-class and out-of-class activities. As academic teachers–researchers, we designed a semester-long course in which academic and out-of-university activities interact and overlap. The data were collected at the end of the course from student reports (diaries) and audio-recorded semi-structured interviews inspired by the elicitation interview technique. This technique involves a fine-grained description of the lived experience. We present selected excerpts in which students described their boundary-crossing movements between academic and out-of-university activities. Data were evaluated using a purpose-built analysis approach comprising two macro-categories and three sub-categories of students’ boundary-crossing movements. The results showed that specific learning processes emerged and developed through these movements. Implications for teaching and learning are highlighted.